2016
DOI: 10.1016/j.psyneuen.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Basal testosterone, leadership and dominance: A field study and meta-analysis

Abstract: This article examines the role of basal testosterone as a potential biological marker of leadership and hierarchy in the workplace. First, we report the result of a study with a sample of male employees from different corporate organizations in the Netherlands (n=125). Results showed that employees with higher basal testosterone levels reported a more authoritarian leadership style, but this relationship was absent among those who currently held a real management position (i.e., they had at least one subordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 61 publications
(78 reference statements)
3
31
0
Order By: Relevance
“…The effect size for basal testosterone's association with the number of dove choices can be approximated by the correlation reported in Table 2 (r = 0.23; approximately 5.3% of the variance in the number hawk decisions is explained by basal testosterone levels). This observed effect size is similar to the effect sizes reported in previous research on basal testosterone's direct association with social behavior or decision making (e.g., r's between 0.21 and 29, Slatcher et al, 2011; standardized beta estimate of 0.26, Ronay and Carney, 2013; r's in the 0.20 to 0.30 range, Turan et al, 2014;r = 0.11, Platje et al, 2015;r = 0.11, Mehta et al, 2015d; standardized beta estimate of 0.18, van der Meij et al, 2016). At the same time, it is important to acknowledge that a partner's number of hawk decisions was a much stronger predictor of a player's own hawk decisions (r = 0.65; McClintock and Liebrand, 1988).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect size for basal testosterone's association with the number of dove choices can be approximated by the correlation reported in Table 2 (r = 0.23; approximately 5.3% of the variance in the number hawk decisions is explained by basal testosterone levels). This observed effect size is similar to the effect sizes reported in previous research on basal testosterone's direct association with social behavior or decision making (e.g., r's between 0.21 and 29, Slatcher et al, 2011; standardized beta estimate of 0.26, Ronay and Carney, 2013; r's in the 0.20 to 0.30 range, Turan et al, 2014;r = 0.11, Platje et al, 2015;r = 0.11, Mehta et al, 2015d; standardized beta estimate of 0.18, van der Meij et al, 2016). At the same time, it is important to acknowledge that a partner's number of hawk decisions was a much stronger predictor of a player's own hawk decisions (r = 0.65; McClintock and Liebrand, 1988).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Research in humans also demonstrates connections between testosterone and status-seeking behavior (for reviews, see Mazur and Booth, 1998;Archer, 2006;Eisenegger et al, 2011;Hamilton et al, 2015). Both endogenous testosterone and exogenously elevated testosterone are positively related to markers of dominance motivation (van Honk et al, 2001;Schultheiss et al, 2005;Josephs et al, 2006;Hermans et al, 2008;Bos et al, 2012;Terburg et al, 2012;Terburg and van Honk, 2013;Goetz et al, 2014;Enter et al, 2014;Radke et al, 2015;Mehta et al, 2008;Zilioli and Watson, 2013;van der Meij et al, 2016), aggressive behavior (Carré et al, 2009;Carré and Olmstead, 2015), competitive behavior Carré and McCormick, 2008;Mehta et al, 2008Mehta et al, , 2009Slatcher et al, 2011;Mehta et al, 2015bMehta et al, , 2015cReimers and Diekhof, 2015;Hahn et al, 2016;Eisenegger et al, 2016), and reduced prosocial behaviors including trust, perspective-taking, cooperation, and empathy (Hermans et al, 2006;Mehta et al, 2009;Bos et al, 2010;van Honk et al, 2011;Boksem et al, 2013;Wright et al, 2012;Ronay and Carney, 2013;Edelstein et al, 2014).…”
mentioning
confidence: 99%
“…105 Recently, measurements of testosterone are widely used in assessing the degree of aggression, depression, violence, and antisocial behavior in psychiatry. 106,107 Nephrology. Currently, the levels of salivary creatinine in saliva can be determined in order to monitor renal functions, and to ascertain the efficacy of dialysis in patients with end-stage terminal renal disease.…”
mentioning
confidence: 99%
“…In all patients, changes in salivary testosterone levels were not significantly correlated with changes in any behavioral symptom or index of the CPT. Some studies have suggested that testosterone causes physiological alteration but does not necessarily cause ADHD-like manifestations (Dorn et al, 2009; Rice, 2015; van der Meij et al, 2016). The finding of our study supports this point of view.…”
Section: Discussionmentioning
confidence: 99%